2020
DOI: 10.3390/ma13245664
|View full text |Cite
|
Sign up to set email alerts
|

Cuspal Deflection and Temperature Rise of MOD Cavities Restored through the Bulk-Fill and Incremental Layering Techniques Using Flowable and Packable Bulk-Fill Composites

Abstract: Background: The aim of this study was to investigate cuspal deflection caused by material shrinkage and temperature rise occurring in the pulp chamber during photopolymerization. The aim of this study was also to investigate the effect of flowable and packable bulk-fill composites on cuspal deflection occurring in mesio-occlusal–distal (MOD) cavities restored through the bulk-fill or through the incremental layering technique. Additionally, mechanical and thermal properties of bulk-fill composites were conside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…The thickness of the bucco-lingual cavity was 3 mm measured with a digital caliper (Mitutoyo, Takatsuku, Kawasaki, Japan). Teeth were then subjected to an adhesive procedure by acid etching of enamel and dentin for 30 s and 15 s, respectively, using 37% phosphoric acid (Gerhò, Bolzano, Italy) and subsequentially 5 s of rinsing and drying; finally, the application of the Optibond SE (Kerr Corporation) adhesive system and photo-curing with the Swiss Master Light (EMS) curing unit at an intensity of 1000 mW/cm 2 [ 22 ] SonicFill was directly dispensed into dental cavities using the Sonicfill (Kerr Corporation) handpiece.…”
Section: Methodsmentioning
confidence: 99%
“…The thickness of the bucco-lingual cavity was 3 mm measured with a digital caliper (Mitutoyo, Takatsuku, Kawasaki, Japan). Teeth were then subjected to an adhesive procedure by acid etching of enamel and dentin for 30 s and 15 s, respectively, using 37% phosphoric acid (Gerhò, Bolzano, Italy) and subsequentially 5 s of rinsing and drying; finally, the application of the Optibond SE (Kerr Corporation) adhesive system and photo-curing with the Swiss Master Light (EMS) curing unit at an intensity of 1000 mW/cm 2 [ 22 ] SonicFill was directly dispensed into dental cavities using the Sonicfill (Kerr Corporation) handpiece.…”
Section: Methodsmentioning
confidence: 99%
“…After cavity preparation, teeth were subjected to an adhesive procedure: acid etching (enamel and dentine etching for 30 s and 15 s, respectively) using 37% phosphoric acid (Super etch, SDI, Australia), rinsing and drying for 5 s with an absorbent. After that, a drop of adper 3M adhesive system (Adper adhesive system, 3M ESPE Filtek, St. Paul, MN USA) was applied, and gentle air thinned the bond layer, then photopolymerized for 10 seconds by light cure (radii plus, SDI, Australia) with an intensity of 2100 mW/cm2that was checked by a radiometer (SDI, Australia) for each restoration (6,16).…”
Section: Adhesive Protocol and Matrix Placementmentioning
confidence: 99%
“…The cuspal deflection of restored teeth is one of the clinical implications of polymerization shrinkage stresses produced by the composite resin restorations (6,23). Numerous factors can affect the cuspal deflection of a tooth, such as the type of tooth, cavity design and amount of remaining tooth structure (6,24), curing mode (25), and the type of resin composite material (6,10). The current study showed an inward cuspal deflection for all subgroups.…”
Section: Cuspal Deflectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, manufacturers have also highlighted that this class of materials exhibits lower polymerization shrinkage compared to flowable and conventional RBC counterparts [ 6 ]. Consequently, complications associated with polymerization shrinkages [ 7 ] such as secondary caries [ 8 , 9 ], postoperative sensitivity, pulpal irritation [ 10 ], or cusp deflections [ 11 , 12 ] are likely to be reduced.…”
Section: Introductionmentioning
confidence: 99%